13-(8x)+4x-(-12)=

Simple and best practice solution for 13-(8x)+4x-(-12)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-(8x)+4x-(-12)= equation:


Simplifying
13 + -1(8x) + 4x + -1(-12) = 0

Remove parenthesis around (8x)
13 + -1 * 8x + 4x + -1(-12) = 0

Multiply -1 * 8
13 + -8x + 4x + -1(-12) = 0

Multiply -1 * -12
13 + -8x + 4x + 12 = 0

Reorder the terms:
13 + 12 + -8x + 4x = 0

Combine like terms: 13 + 12 = 25
25 + -8x + 4x = 0

Combine like terms: -8x + 4x = -4x
25 + -4x = 0

Solving
25 + -4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-25' to each side of the equation.
25 + -25 + -4x = 0 + -25

Combine like terms: 25 + -25 = 0
0 + -4x = 0 + -25
-4x = 0 + -25

Combine like terms: 0 + -25 = -25
-4x = -25

Divide each side by '-4'.
x = 6.25

Simplifying
x = 6.25

See similar equations:

| x^2+25x-300=0 | | 5x+2(5x-15)=60 | | -6v=-16v+30 | | 10-16x=-230 | | 4-6(4n+1)= | | x/4=x/5-7 | | 6(-2+7x)+4x=36-2x | | 2(2.5x-5)+2= | | -8a+10=-8(a+3) | | n=-3/8=1/8 | | 2+(5+y)=0 | | 9(-8-2p)= | | -4+8(p+4)=4(4p-1) | | 15-9/3=-9 | | 14x-14=16x | | 10-3a=40 | | 81[(5+3)-5]= | | Y^2-9y=-18 | | 4t+9= | | -4(5-4x)=-40+6x | | -7=a-7 | | 7(m-7)=28-4m | | 33-3n=-6(n-8) | | -17=15n-20 | | 11m+10=9m | | 60=log(x) | | 4=4x+9 | | -3(n-4)-3=3-(n+2) | | 7x+1=1+8x | | ab+5a-b-5=0 | | 18(v+3)-2v=4(4v+1)-11 | | 6/5:2,7 |

Equations solver categories